A digital pedagogy pivot: re-thinking higher education practice from an HRD perspective. Issue 4 (7th August 2020) - Anderson, Valerie
ABSTRACT: This paper has a provocative purpose. From both HRD and academic practice perspectives, it considers the digital pedagogy pivot made necessary by the Covid-19 pandemic. Universities have traditionally resisted substantial change in learning and teaching processes. This paper addresses the challenge they face of achieving the equivalent of a ten-year digital learning strategy in mere months. From a position that HE pedagogy constitutes a site of HRD practice, the paper considers the characteristics of a meaningful, digitally enabled pedagogy in Higher Education (HE) and their alignment with established HRD theories and concepts. It considers the pedagogic opportunities arising from the 'digital pivot' and the HRD processes appropriate to facilitate game-changing approaches to academic practice in Higher Education. The paper advances debate about the relationship between HRD and HE academic practice and contributes proposals for HRD processes to support rapid pedagogic change. It further contributes an original categorization of the way in which HRD concepts and theories are aligned with principles of HE pedagogy and a digital pedagogy pivot model.